Training video on the integration of the leguminous Mucuna cover crop in coffee and banana systems in central Africa. - Ntamwira, Jules Bagula; Kitumaini Safari, Nancy; Blomme, Guy; Katera, Issa; Ocimati, Walter (2024)
Mucuna pruriens is a shade- and drought-tolerant, fast-growing nitrogen-fixing cover crop that has been shown to contribute to increased farm productivity, restoration of degraded lands through improving soil physical, chemical, and biological properties and carbon sequestration in banana and coffee fields in eastern Democratic Republic of Congo. Mucuna in banana and coffee systems can also reduce weed burden, improving the quality of life for women and children who provide most of the labor for weeding. This video captures success stories of using Mucuna as a cover crop on station and on farm in eastern DR Congo and will serve as a tool for transforming the mindset of farmers during scaling of the innovation. The video will also be regularly updated to capture new success stories and case studies.